Flavoring compounds and wood molasses in growing-finishing rations - Koch, B.A.; Loeppke, D.W. (Kansas Agricultural Experiment Station, 2011)
Two flavoring compounds, monosodium glutamate (MSG) and flance, were used separately and in combination in rations for growing-finishing swine. Wood molasses, a source of energy, was used with the two flavoring compounds. Sixty –three pigs were used. Each pen of 9 pigs was confined to a concrete-floored pen in building M. Feed and water were available at all times. All rations were pelleted, with the test ingredients replacing sorghum grain in the formulation.
Keywords: Swine; Monosodium glutamate (MSG); Wood molasses; Performance